The Utility of GIS for Identifying Areas of Recreation Conflict for Targeted Interpretive Messaging. Issue 2 (November 2020) - Peterson, Brian A.; Sharp, Ryan L.; Fefer, Jessica P.; Brunson, Michael A.
Past research has extensively studied interpretive messaging and visitor conflict within parks and protected areas. However, comprehensive understanding of how to identify trailside interpretive sign locations is lacking. The purpose of this study was to introduce an approach using geographic information systems (GIS) that supplements decision-making regarding sign placement. The study site was Grand Canyon National Park's Rim to Rim (R2R) corridor. To identify sign placement locations, two analytical phases were conducted. First, GPS data loggers were distributed to visitors and their travel patterns were analyzed for spatial behaviors and spatial interactions that are known to influence the likelihood of recreation conflict. Specifically, locations with a high variance of visitor travel speeds and locations with concentrated visitor use were identified. Second, geographic data were analyzed to identify locations for a combination of features that together influence the likelihood of recreation conflict. Specifically, popular bidirectional trail segments with significant elevation change were identified. We reported these locations and areas using GPS coordinates for evaluation by future research. This research was a necessary step towards comprehensively understanding how to identify locations for interpretive signs.